2021
DOI: 10.1101/2021.03.29.21253871
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NTRK oncogenic fusions are exclusively associated with the serrated neoplasia pathway in the colorectum and begin to occur in sessile serrated lesions

Abstract: Background: NTRK fusions are emerging tissue-agnostic drug targets in malignancies including colorectal cancers (CRCs), but their detailed landscape in the context of various colorectal carcinogenesis pathways remains to be investigated. Methods: Pan-TRK expression was assessed by immunohistochemistry in retrospectively collected colorectal epithelial tumor tissues, including 441 CRCs (133 microsatellite instability-high (MSI-high) and 308 microsatellite stable (MSS)) and 565 premalignant colorectal lesions (3… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 51 publications
(125 reference statements)
1
4
0
Order By: Relevance
“…Additionally, several other NGS-based studies have suggested 2.6-7.3% occurrence of NTRK fusions in dMMR/MSI CRCs [15,16,18,20,21]. In the dMLH1/BRAFV600Ewt subgroup, frequency of NTRK fusions has been reported to be 5-28% [4,16,17] and in the subgroup of dMLH1/MLH1ph 14-19% [18,19], which are in line with our frequencies of 11% (7/62) and 16% (7/43), respectively. Yet other studies have reported NTRK fusions to occur in dMLH1/BRAFV600Ewt/MLH1ph/RASwt subgroup of CRC with as high frequency as 17-44% [15][16][17][18]22] being comparable to our prevalence of 23.3% (7/30).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Additionally, several other NGS-based studies have suggested 2.6-7.3% occurrence of NTRK fusions in dMMR/MSI CRCs [15,16,18,20,21]. In the dMLH1/BRAFV600Ewt subgroup, frequency of NTRK fusions has been reported to be 5-28% [4,16,17] and in the subgroup of dMLH1/MLH1ph 14-19% [18,19], which are in line with our frequencies of 11% (7/62) and 16% (7/43), respectively. Yet other studies have reported NTRK fusions to occur in dMLH1/BRAFV600Ewt/MLH1ph/RASwt subgroup of CRC with as high frequency as 17-44% [15][16][17][18]22] being comparable to our prevalence of 23.3% (7/30).…”
Section: Discussionsupporting
confidence: 90%
“…Westphalen et al found CRC to be the only cancer type in which NTRK fusions are associated with sporadic MSI [7]. Interestingly, Kim et al have recently described that NTRK fusions in CRC develop along the serrated pathway, in which sporadic dMLH1 is a major molecular event, and these fusions can already be present in premalignant sessile serrated lesions [19]. Additionally, several other NGS-based studies have suggested 2.6-7.3% occurrence of NTRK fusions in dMMR/MSI CRCs [15,16,18,20,21].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies have revealed that miR-107 promotes cancer progression by inhibiting Phosphatase and Tensin Homolog Deleted on Chromosome Ten (PTEN) expression (40,41). As for TPM3, considerable research attention has been paid to the fact that TPM3 can participate in gene fusion and rearrangement, such as TPM3-NTRKs (10,11,42), TPM3-ROS1 (12,43), and so on. Although the proportion is not high, TPM3 rearrangement is often accompanied by special therapeutic effects (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…The TPM3 protein can interact with actin, affecting muscle cell contraction and other cytoskeletal activity (8,9). Meanwhile, TPM3 gene-related rearrangement has been widely reported in malignant tumors and other diseases, such as colorectal cancer, thyroid cancer, and lung cancer (10)(11)(12). Some proteomics-based studies have found that TPM3 expression is abnormal in a variety of cancers and may influence tumor behaviors and therapeutic resistance (13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…As a matter of topical interest and therapeutic relevance, findings of a recent study by Kim et al [5] concluded that NTRK-rearranged colorectal carcinomas progress exclusively via the serrat-ed pathway of neoplasia, thus expanding the molecular landscape of serrated colorectal lesions. To the best of our knowledge, oncogenic gene fusions including NTRK fusions have yet to be studied in serrated lesions in IBD, and would indeed form an interesting research question.…”
mentioning
confidence: 99%